Ultra-Processed Food and the Risk of Obesity Among Urban Youth - Andi Nur Arifah Apriani; Seno Lamsir (Journal of Public Health Indonesian, 2025)
Ultra-processed food (UPF) consumption has risen sharply among urban adolescents in Indonesia due to the modernization of food environments, digital media exposure, and lifestyle transitions. This study examines the relationship between UPF consumption and adolescent obesity using a PRISMA-guided Systematic Literature Review (SLR), synthesizing 58 eligible articles from an initial 612 publications. Findings indicate that UPF consumption is driven by high accessibility, low cost, pervasive digital marketing, obesogenic school environments, and socio-cultural preferences that normalize fast-food intake. Physiologically, UPFs are energy-dense, low in fiber, and contain additives and added sugars that impair appetite regulation, contributing to excessive caloric intake and adiposity. Behavioral mechanisms such as screen-time snacking, emotional eating, and peer influence further exacerbate weight gain risks. Moreover, urban food environments with dense concentrations of convenience stores and fast-food outlets restrict access to healthier options. The study concludes that reducing adolescent obesity requires multi-level strategies including UPF marketing regulations, healthy school food zoning, digital nutrition education, and structural improvements to urban food environments. These findings underscore the need for comprehensive interventions to reduce UPF consumption and enhance urban adolescent health outcomes in Indonesia